DETERMINATION OF CORPORATE PROFIT THROUGH TIME DEPOSITS AND SHARE OWNERSHIP IN PT PRUDENTIAL LIFE DETERMINATION OF CORPORATE PROFIT THROUGH TIME DEPOSITS AND SHARE OWNERSHIP AT PT PRUDENTIAL LIFE - Khairani; Fransiska Sirait (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the effect of time deposits and stock ownership on PT Prudential Life's profit for the 2015–2025 period. The study uses a quantitative approach with secondary data in the form of quarterly financial reports totaling 44 observations. The data analysis technique uses multiple linear regression with t-test, F-test, and coefficient of determination (R²). The results show that time deposits have no significant effect on company profits, while stock ownership has a positive and significant effect on company profits. Simultaneously, time deposits and stock ownership have a positive and significant effect on PT Prudential Life's profit with a coefficient of determination of 94.5%.